2023
DOI: 10.1055/a-2161-0105
|View full text |Cite
|
Sign up to set email alerts
|

E-cigarette use-associated lung injury (EVALI)

Nathaly Yessenia Tituana,
Claudia Gabriela Clavijo,
Evelyn Fernanda Espinoza
et al.

Abstract: The prevalence of vaping has overtaken conventional cigarettes as the most frequent form of nicotine consumption among 15–24-year olds. There are currently a large number of both legitimate and illegitimate products and suppliers offering more than 8000 different flavors of vape on the market, whose additives are not tested, studied or regulated and whose safety and toxicity profile remains unknown. In vitro studies have demonstrated a dose-dependent decrease in the viability of normal human bronchial epitheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…While PG and VG are deemed ‘generally recognized as safe’ (GRAS) by the FDA for food additives, their safety is established in the context of consumption. However, when subjected to alternative routes of administration, particularly inhalation, additional risks arise [ 12 , 13 , 14 ]. For example, recent research has shown that non-phthalate plasticizers can induce endocrine-disrupting effects by engaging mechanisms regulated by NRs [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…While PG and VG are deemed ‘generally recognized as safe’ (GRAS) by the FDA for food additives, their safety is established in the context of consumption. However, when subjected to alternative routes of administration, particularly inhalation, additional risks arise [ 12 , 13 , 14 ]. For example, recent research has shown that non-phthalate plasticizers can induce endocrine-disrupting effects by engaging mechanisms regulated by NRs [ 15 ].…”
Section: Introductionmentioning
confidence: 99%